Biases in the reporting of labour market dynamics - Gillian Paull (Institute for Fiscal Studies (IFS), 2002)
Correctly measuring individual dynamics in labour market behaviour has become increasingly important as research and policy attention has become more focused on the relationships between current employment opportunities and past experience. Surveys collecting information on labour market histories use repeated interviews and retrospective reporting, laying the resulting data open to potential biases from spurious transitions due to random measurement errors and from systematic recall error. This paper uses a unique data opportunity provided by the British Household Panel Survey to systematically investigate the impact of recall on measured labour market behaviour and to highlight how and to what degree the biases in the reported data may affect the estimation of models of labour market dynamics. The results allow analysts to judge whether conclusions drawn from such models are likely to be compromised by the reporting biases.
Keywords: J60; J64; C8; 330; labour market dynamics; recall bias; Arbeitsmarkt; Arbeitsmarktsegmentierung; Geschlecht; Ethnische Gruppe; Großbritannien